The relationship between language learning anxiety and language learning strategy use with language proficiency in computer-aided english language learning environment among tertiary students in China - Wang, Fei (2020)
Research on the relationship between English language learning anxiety (LLA) and English language learning strategy (LLS) in computer-aided language learning (CALL) environment is considerably lacking. The interference of English language learning anxiety and the lack of effective English language learning strategy are two challenges for Chinese students during the process of language learning in computer-aided language learning environment. The study investigated the relationship between English language learning anxiety and English language learning strategy in computer-aided language learning environment. Besides, the relationship between English language learning anxiety and English proficiency, and the relationship between English language learning strategy and English proficiency in computer-aided language learning environment were revealed in this study. The quantitative method was employed, which involved 422 English major undergraduate students. English Language Learning Anxiety in CALL Environment Questionnaire and English Language Learning Strategy in CALL Environment Questionnaire were adopted as the instruments. The results indicated: firstly, a negative relationship between English language learning anxiety and English language learning strategy use; secondly, a positive relationship between English language learning strategy and English proficiency; and, finally, a negative relationship between English language learning anxiety and English proficiency in computer-aided language learning environment among English major undergraduates in China. English major students sometimes experienced English LLA, especially comprehensive anxiety, communication apprehension and computer internet anxiety. Memory strategy, affective strategy and social strategy were less frequently used in CALL environment. The level of English LLA and the frequency of English LLS employed in CALL environment were not related to gender, personality, family background, but significantly related to interest and confidence. The results indicated: firstly, a negative relationship between English language learning anxiety and English language learning strategy use; secondly, a positive relationship between English language learning strategy and English proficiency; and, finally, a negative relationship between English language learning anxiety and English proficiency in computer-aided language learning environment among English major undergraduates in China.